Ethical Leadership, Work Stress, and Teacher Performance: Moderated by Psychological Capital in Elementary to Senior High Schools - Elisabeth Supriharyanti; Sarwanti Purwandari; Annisa Alfa Setyawan (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2026)
Ethical leadership has increasingly attracted attention as an important factor in promoting positive work outcomes and organizational effectiveness. In educational institutions, teacher performance plays a critical role in ensuring educational quality and student success. This study aims to examine the relationships among ethical leadership, work stress, psychological capital, and teacher performance. An explanatory research design was employed to test the proposed hypothesis and explain the relationships among variables. The sample consisted of 114 teachers from Elementary-Senior High school (SD–SMA) level SPK schools in Surabaya. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The empirical findings indicate that ethical leadership has no significant direct effect on teacher performance. However, ethical leadership significantly reduces teachers' work stress, and lower work stress leads to higher teacher performance. Furthermore, work stress significantly mediates the relationship between ethical leadership and teacher performance. In contrast, psychological capital does not moderate the relationship between work stress and teacher performance.